Les transformations du culte impérial romain au IVe siècle : entre continuité et adaptation - Beauchemin-Brisson, Étienne (Université de Montréal, 2022)
The study of the Roman imperial cult in the 4th century has often been relegated to the background in research relating to this subject. The imperial cult has even often been relegated to the same fate than the rest of the Roman traditional cults. However, in the light of period sources and the work of certain historians, such as Louis Bréhier, the imperial cult seems to have survived this prognosis of disappearance. More interesting still, the imperial cult appears to have transformed and adapted to the new reality offered by a Christianizing Roman Empire while the power of the emperor was becoming more sacred. The work presented in this thesis parallels the metamorphosis experienced by the imperial cult with the strengthening of imperial power during the fourth century, while comparing the evolution of the perception that Christians had of this fundamentally traditional institution. As mentioned above, the study is based on a body of contemporary sources, ranging from Christian homilies to epigraphic sources which will corroborate the information found in the work of several historians who have studied the topic. Overall, this research demonstrates that the imperial cult succeeded in shedding religious connotations that Christians considered problematic while continuing to function and occupy a central place in the life of the Romans. This, together with an imperial power expressed in absolute terms, initiated the metamorphosis of the imperial cult into a "monarchical cult", exalting even more the emperor's power for centuries to come.
Keywords: 4th century; Ancient history / Histoire de l’Antiquité (UMI : 0579); Ancient religion; Antiquité tardive; Christianisme antique; Culte impérial; Early Christianity; Empire romain; IVe siècle; Imperial cult; Imperial power; Late antiquity; Pouvoir impérial; Religion antique; Roman Empire